The strength of negative plant–soil feedback increases from the intraspecific to the interspecific and the functional group level. Issue 4 (26th January 2018) - Bukowski, Alexandra R.; Schittko, Conrad; Petermann, Jana S.
Abstract: One of the processes that may play a key role in plant species coexistence and ecosystem functioning is plant–soil feedback, the effect of plants on associated soil communities and the resulting feedback on plant performance. Plant–soil feedback at the interspecific level (comparing growth on own soil with growth on soil from different species) has been studied extensively, while plant–soil feedback at the intraspecific level (comparing growth on own soil with growth on soil from different accessions within a species) has only recently gained attention. Very few studies have investigated the direction and strength of feedback among different taxonomic levels, and initial results have been inconclusive, discussing phylogeny, and morphology as possible determinants. To test our hypotheses that the strength of negative feedback on plant performance increases with increasing taxonomic level and that this relationship is explained by morphological similarities, we conducted a greenhouse experiment using species assigned to three taxonomic levels (intraspecific, interspecific, and functional group level). We measured certain fitness‐related aboveground traits and used them along literature‐derived traits to determine the influence of morphological similarities on the strength and direction of the feedback. We found that the average strength of negative feedback increased from the intraspecific over the interspecific to the functional group level. However, individual accessions and species differed in the direction and strength of the feedback. None of our results could be explained by morphological dissimilarities or individual traits. Synthesis . Our results indicate that negative plant–soil feedback is stronger if the involved plants belong to more distantly related species. We conclude that the taxonomic level is an important factor in the maintenance of plant coexistence with plant–soil feedback as a potential stabilizing mechanism and should be addressed explicitly in coexistence research, while the traits considered here seem to play a minor role. Abstract : We tested plant–soil feedback, a suggested mechanism of plant coexistence, at three taxonomic levels within the same experiment. We found that its strength increased from the intraspecific over the interspecific to the functional group level indicating a role in diversity maintenance within and between species.